JADA: A graphical user interface for comprehensive internal dose assessment in nuclear medicine. Issue 7 (19th June 2013) - Grimes, Joshua; Uribe, Carlos; Celler, Anna
Abstract : Purpose: : The main objective of this work was to design a comprehensive dosimetry package that would keep all aspects of internal dose calculation within the framework of a single software environment and that would be applicable for a variety of dose calculation approaches. Methods: : Our MATLAB‐based graphical user interface (GUI) can be used for processing data obtained using pure planar, pure SPECT, or hybrid planar/SPECT imaging. Time‐activity data for source regions are obtained using a set of tools that allow the user to reconstruct SPECT images, load images, coregister a series of planar images, and to perform two‐dimensional and three‐dimensional image segmentation. Curve fits are applied to the acquired time‐activity data to construct time‐activity curves, which are then integrated to obtain time‐integrated activity coefficients. Subsequently, dose estimates are made using one of three methods. Results: : The organ level dose calculation subGUI calculates mean organ doses that are equivalent to dose assessment performed by OLINDA/EXM. Voxelized dose calculation options, which include the voxel S value approach and Monte Carlo simulation using the EGSnrc user code DOSXYZnrc, are available within the process 3D image data subGUI. Conclusions: : The developed internal dosimetry software package provides an assortment of tools for every step in the dose calculation process, eliminating the need for manual data transfer between programs. This saves times and minimizes user errors, while offering a versatility that can be used to efficiently perform patient‐specific internal dose calculations in a variety of clinical situations.